TANGGUNG JAWAB PELAKU USAHA YANG MENJUAL DAGING TIDAK LAYAK KONSUMSI DI PASAR TRADISIONAL DUPA KOTA PEKANBARU - Dita Aprianty; Evi Deliana; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
One type of business actor is a business actor who sells meat, especially in traditional markets. Meat is an animal food that is liked by all levels of society because it tastes delicious and is highly nutritious. consumer trust is often used by businesses by cheating or taking advantage unilaterally, namely providing unworthy consumption of meat from what has been promised to consumers who will buy the meat.the type of research used in writing this law is sociological legal research which is a study of the effectiveness of the law that is in effect or research on legal identification. Whereas if seen from the nature of this research is descriptive. This study uses primary data, namely data obtained from the field through interviews and secondary data, namely data that has been prepared.The results of this study are the way traders carry out consumption and sale of meat that is fit for consumption in accordance with the law is that safe, healthy, whole and halal meat (ASUH) is meat that is expected by all consumers, because from various aspects ASUH chicken meat is guaranteed if consumed by the community.as stipulated in Government Regulation No. 22 of 1983 concerning Veterinary Public Health, it is stipulated that meat that is fit for human consumption must meet the requirements of safe, healthy, whole and halal (ASUH). the responsibility of the business actor who sells meat that is not suitable for consumption in the traditional market of Dupa in Pekanbaru is in accordance with Article 19 paragraph (1) of the Consumer Protection Act which is compensation in the form of refunds or replacement of similar goods and / or services orequal value, or health care and / or compensation that is in accordance with the provisions of the applicable legislation.Keywords: Responsibility, Business Actors, Meat Not Consumption